A multi-disciplinary meta-review of the public–private partnerships research. Issue 2 (1st February 2020) - Narbaev, Timur; De Marco, Alberto; Orazalin, Nurlan
Abstract: Public-private partnerships (PPP) research is very diverse. This field of research covers different topics across multiple disciplines and is disseminated in many journals. This has led to numerous review studies with a single discipline focus that apply mostly subjective or descriptive analyses. With the purpose of providing an integrated overview of all the disciplines that involve PPP and uncovering connections between these, this research provides an extensive PPP literature meta-review that uses objective bibliometric measures on 1970 articles from 773 journals. The methodology involves ranking journals, identifying topical trends over 1989–2018, and clustering the literature to create a PPP knowledge map with associated research domains. The findings reaffirm that PPP is not only a multi-disciplinary research area but also a self-contained meta-discipline that integrates some allied disciplines with their foundational theories. The PPP meta-discipline is largely dominated by Construction Management and Economics (CME), Public Administration and Management, and Transportation Research disciplines, and integrates emerging topics such as sustainability, governance and stakeholders management. This study contributes to the CME scholarly community as it offers the first comprehensive meta-analysis of PPP literature and helps understanding PPP under the lens of a multi-disciplinary perspective.